Urbanization, Migration and the Demise of Malay Settlement - Julaihi, Wahid; Azli, Abdullah (2021)
The need for a better quality of life is driving the pace of urbanization in our country. Today, almost 80 per cent of Malaysians choose a metropolis area as their residence, which is arguably far beyond the rate of world urbanization currently at 55 per cent. The loss of Malay craftsmanship and Malay settlements are related to the issue. The current study employed socio-economic data from 350 local respondents from a survey in April 2019 and were analysed using IBM SPSS V26 supported by interview techniques and pictorial documentation. Mapping techniques are performed using the Google Earth application to generate existing settlements patterns. Finally, AutoCAD 2018 software is used to portray the current pattern of the case study area. The study establishes that urbanization and migration by the young generation destroy Malay settlements and craftsmanship skills.